Struggling with God : Kierkegaard and the temptation of spiritual trial - Podmore, Simon D., 1977- (James Clark & Company, 2013)
Invoking the biblical motif of Jacob's struggle with the Face of God (Genesis 32), Simon D. Podmore undertakes a constructive theological account of 'spiritual trial' (tentatio; known in German mystical and Lutheran tradition as Anfechtung) in relation to enduring questions of the otherness and hiddenness of God and the self, the problem of suffering and evil, the freedom of Spirit, and the anxious relationship between temptation and ordeal, fear and desire. This book traces a genealogy of spiritual trial from medieval German mystical theology, through Lutheran and Pietistic thought (Tauler; L.